ANALYSIS OF RAT PLATELET COUNT AFTER ELECTRICAL EXPOSURE IN ACUTE AND SUBACUTE PHASE OF BURN INJURY - F P H, Fransiska Nooril; Elfiah, Ulfa; Indreswari, Laksmi; Wisudanti, Desie Dwi (Universitas Airlangga, 2019)
Highlights: In the acute phase of electric burn injury, there was a significant change in platelet count. Contrarily, no significant change in platelet count was observed during the subacute phase of electric burn injury. Abstract: Introduction: Electrical burns are one of the causes of important health burdens throughout the world with incidences varying between 4–18% of all burns. In electrical burns, blood vessels are the heavily damaged tissue characterized by endothelial erosion, followed by adhesion and aggregation of platelets to form a hemostatic plug. The screening test for assessing the formation of a hemostatic plug is platelet count. Platelet count monitoring is very important during the resuscitation phase and treatment periods in severe burns, namely in acute and subacute phases of burns. The purpose of this study is to determine and analyze the changes in the platelet count of rats after electrical exposure in the acute and subacute phases of burns. Methods: This is a quasi-experimental study in vivo with post-test-only group design. The control group in this study was not given electrical exposure and the rat's blood was taken directly after the adaptation process. In the other five groups, P1, P2, P3, P4, and P5 were exposed to 140 V for 17 seconds, then their blood was taken for platelet counts on days 0, 3, 7, 10, and 14 post-exposure. Results : The result of this study based on a Post Hoc LSD test showed that there was a change of platelet number after exposure in the acute phase of burn injury and there was no change of platelet number after exposure in the burning subacute phase. Conclusions: Platelet count difference in acute phase of electric burn injury and no difference in platelet count difference in subacute phase of electric burn injury.